Implementation of the 5s methodology for inventory management in an infirmary of a public hospital - Souza, Laura Ferreira Morais de; Guimarães, Camille Pereira; Pimentel , Cristiane Agra (Brazilian Journal of Production Engineering, 2025)
The application of Lean Healthcare tools aims to reduce waste and standardize the flow of production areas. Inventory management in a ward requires an organization consistent with the care that will be provided to patients, with the 5S tool as an aid to improve health support. The objective of this study was to implement 5S in a ward to standardize and optimize inventory, using Lean Healthcare to assist professionals in improving the quality of the service that will be provided. Action research and a case study in a Maternal and Child Hospital in Feira de Santana were used as methodology. The implementation of the tool, such as material traceability, was one of the factors available to obtain the expected result. As a preventive measure, the proposed improvements reduce material waste, contributing to improved care.
Keywords: 5s; Improvement; Lean; Quality